President's address - Findlater, William (Statistical and Social Inquiry Society of Ireland, 1892)
It occurred to me that it might possibly be pleasing both to the members of this society and that portion of the outside public which takes an interest in our proceedings, if in my address I endeavoured to make some general observations upon that method or science which our society has been formed to cultivate and support. It must not be supposed for a moment that I hope to communicate anything novel to the members of this society, most of whom are far more familiar with every branch of the subject than I am. Nevertheless it may be of use even to them to refresh their memories as to matters which they may have forgotten, and possibly it may be the means of inducing the outsiders to whom I have referred to take a larger interest in the objects of our society, and lead to their joining our ranks, thereby enabling us to increase our influence and efforts in the cause of social reform. I, therefore, propose to make some observations upon statistics.
Read Tuesday, 24th May, 1892
Keywords: Statistical methods; Quantitative methods; 314.15